2021
DOI: 10.3390/antiox10020217
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Sperm Mitochondrial Respiration Efficiency by Plant Polyphenols

Abstract: Plant bioactives, such as polyphenols, can differentially affect (positively or negatively) sperm quality, depending on their concentration. These molecules have been proposed as natural scavengers of reactive oxygen species (ROS) for male infertility treatment. However, few data are available about their effects on the molecular mechanisms related to sperm quality and, in particular, to sperm mitochondrial function. We investigated the effects of quercetin, naringenin, genistein, apigenin, luteolin, and resve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 78 publications
0
38
0
1
Order By: Relevance
“…Considering that some plant EVs have shown inhibitory effects against pathogenic microorganisms [ 99 ], they may be studied as possible substitutes for antibiotics in the semen preservation process. Recently, several studies reported that some polyphenols can modulate cellular metabolic pathways and transform some compounds into others, exerting not only potent antioxidant effects but also a cascade of secondary protective effects [ 100 , 101 ]. Some polyphenols have been shown to modulate the sperm metabolism by increasing the efficiency of mitochondrial respiration [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that some plant EVs have shown inhibitory effects against pathogenic microorganisms [ 99 ], they may be studied as possible substitutes for antibiotics in the semen preservation process. Recently, several studies reported that some polyphenols can modulate cellular metabolic pathways and transform some compounds into others, exerting not only potent antioxidant effects but also a cascade of secondary protective effects [ 100 , 101 ]. Some polyphenols have been shown to modulate the sperm metabolism by increasing the efficiency of mitochondrial respiration [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported that some polyphenols can modulate cellular metabolic pathways and transform some compounds into others, exerting not only potent antioxidant effects but also a cascade of secondary protective effects [ 100 , 101 ]. Some polyphenols have been shown to modulate the sperm metabolism by increasing the efficiency of mitochondrial respiration [ 100 ]. However, the source of the raw plant material, the extraction method, and the concentration of the plant extract play an important role in its effects on the sperm cell.…”
Section: Discussionmentioning
confidence: 99%
“…En conjunto con otros plaguicidas, incrementa la prevalencia depresión debido a que el uso frecuente de estos altera el campo neurológico con los neurotransmisores (Lugo, 2017); puede causar toxicidad en células placentarias y del hígado, actuar como disruptor endocrino, generar afecciones respiratorias, gastrointestinales, dermatológicas y neurológicas, así como fragmentación del material genético (Salazar y Aldana, 2011). Afecta negativamente la respiración mitocondrial de los espermatozoides con su consecuencia en la infertilidad (Ferramosca et al, 2021). Asimismo, la presencia de glifosato y AMPA en orina de mujeres embarazadas se asocia con partos prematuros (Lesseur et al, 2022).…”
Section: Daños De Los Principales Herbicidas Utilizadosunclassified
“…Genistein (GEN) is an isoflavone with antioxidant and protective effects on impaired mitochondria in PD models [226,227] and is also able to boost mitochondrial energetic function by inducing the expression of genes associated with ATP synthesis [228,229]. However, it has poor aqueous solubility, oral bioavailability and brain accumulation [230], which hinders its therapeutic effects.…”
Section: Nanosystems Containing Antioxidative and Neuroprotective Plant Chemicals To Repair Mitochondrial Function In Neurodegenerationmentioning
confidence: 99%